Strengthening Public Health Systems : Policy Ideas from a Governance Perspective - Khemani, Stuti (World Bank, Washington, DC, 2020)
Public health systems that are capable of disease surveillance and action to prevent and manage outbreaks require trustworthy community-embedded public health workers who are empowered to undertake their tasks as professionals. Economic theory on incentives and norms of agents tasked with performing activities that society cares about yield direct implications for how to recruit and manage frontline health workers to promote trustworthiness and professionalism. This paper provides novel evidence from a survey of public health workers in Bihar, India's poorest state, that supports the insights of economic theory and taken together yields ideas that can immediately be put to work in policy responses to the COVID-19 crisis. These ideas address problems of governance and trust that have bedeviled health policymakers. Managing the current and preventing future pandemics requires going beyond technical health policies to the political institutions that shape incentives and norms of health workers tasked with implementing those policies.